STRATEGI PEMERINTAH KOTA PADANG PANJANG DALAM PEMULIHAN EKONOMI PASCA BENCANA BANJIR BANDANG - Adilla, Raisa; Mubarak, Adil (Penerbit Lafadz Jaya, 2025)
Padang Panjang is a transit city in West Sumatra that frequently experiences rain and is located in a mountainous area. The city has faced economic challenges following the eruption of Mount Marapi on December 3, 2023, and the flash flood in Lembah Anai on May 11, 2024. These disasters cut off the national Padang–Bukittinggi route and disrupted the trade, services, and small business sectors. This study examines the efforts of the Padang Panjang City Government to recover its economy. The research method involved interviews with 16 individuals from various agencies, including Bappeda, City Hall, the Department of Trade, BPBD, disaster response groups, and flood-affected communities. Data were collected from interviews and documents. The results show that the recovery strategy focuses on trade and small businesses. The implementation of these strategies involves inter-agency collaboration, capital assistance, low-cost market operations, infrastructure repairs, and interest subsidies. However, the recovery has not been evenly distributed. Regional revenues in 2024 failed to meet the target, some workers were laid off, small business sales declined, and the distribution of goods was temporarily hampered. Supporting factors for recovery are inter-agency cooperation, budgetary support, and competence of human resources. Obstacles include dependence on aid and issues with access/logistics. This study recommends improving connectivity, expanding small business programs, simplifying interest subsidies, increasing economic literacy among residents, and implementing results-based evaluations to strengthen the city's economic resilience.